UMPSA expands strategic collaboration with Istanbul Kultur University IKU - Mohd Ferdaus, Musa (UMPSA, 2024)
ISTANBUL, 26 February 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) expanded its strategic collaboration with Istanbul Kultur University (IKU), Turkiye, especially in the academic and research fields through the Signing of Memorandum of Understanding (MoU) at IKU campus, Istanbul.